Functional micelles formed by branched polymeric surfactants: Synthesis, characteristics, and application as nanoreactors and carriers. (February 2016) - Riabtseva, Anna; Mitina, Nataliya; Grytsyna, Iryna; Boiko, Nataliya; Garamus, Vasil M.; Stryhanyuk, Hryhoriy; Stoika, Rostyslav; Zaichenko, Alexander
Graphical abstract: Highlights: Branched PEGylated polyelectrolyte surfactants and derived micelles were obtained. Amount and structures of polymer grafted chains are defined by monomer composition. SAXS, DLS, TEM and SEM were used for micelle morphology study. Micelle strong shrinkage caused by binding Dox or Fe2 O3 crystals was revealed. Micelles bearing Dox or Fe2 O3 cause cytotoxic or cytostatic effect on tumor cells. Abstract: Branched polymeric surfactants composed of grafted non-ionic polyethylene glycol (PEG) and anionic polyelectrolyte chains were synthesized via radical polymerization initiated by the comb-like PEG-containing polyperoxide. Above definite concentration in solution, these surfactants form micelle-like structures (MLS). The MLS formed by branched polymeric molecules are of larger size in comparison with size of MLS formed by the initial PEG-containing polyperoxide that is caused mainly by different mechanism of their self-organization and morphology of formed MLS. The availability of grafted polyelectrolyte chains in the MLS provides a possibility of their use as the containers for immobilization of bio-active substances and nucleation of the inorganic nanoparticles, as well as formation of their stable colloidal systems in water in a wide pH range. Noticeable compaction and narrowed size distribution of the MLS were revealed after immobilization of doxorubicin (Dox) molecules or Fe2 O3 nanocrystals. MLS-based systems were used for delivery of Dox and maghemite particles at treatment of tumor cells. Both MLS-based formulations of Dox and Fe2 O3 were efficiently engulfed by rat glioma C6 cells. A significant (10 times) decrease in the effective therapeutic dose of Dox was found when this drug was delivered by a MLS-based formulation of Dox. That effect might be explained by a specific structure and functionality of the novel carrier used for immobilization of drug that should be delivered to target cells.